Mitochondrial cytochrome oxidase C subunit III (cox3) gene as a sensitive and specific target for molecular detection of Babesia gibsoni infection in dogs - Betgiri, Aishwarya A.; Jadhav, Sameer N.; Pawde, Mrunalini; Shukla, Anurag; Mote, Chandrashekhar; Pawar, Prashant D.; Shanmugam, Dhanasekaran; Kundu, Krishnendu (Experimental Parasitology, 2019)
A PCR targeting mitochondrial cytochrome oxidase subunit III (cox3) for molecular detection of Babesia gibsoni infection in dogs has been developed in this study. Fifty blood samples from suspected clinical cases from dogs, brought to the veterinary college clinics, were examined for presence of B. gibsoni using conventional diagnosis by microscopic examination of Giemsa stained thin blood smears. In addition, species specific PCRs targeting ITS-1 region (BgITS-1 PCR) and nested PCR targeting 18S ribosomal RNA gene (Bg18SnPCR) were carried out. A 634 bp PCR fragment of B. gibsoni cox3 gene was amplified in positive samples from three geographical locations of Satara, Wai and Pune in Maharashtra state of India. From analysis of the sequence of the B. gibsoni cox3 gene, we found that the Indian isolate had 96-98% similarity to the isolate from Japan and China. Post sequencing, de-novo diagnostic primer pair for species specific amplification of 164 bp fragment of B. gibsoni cox3 was designed and the PCR was standardized. The diagnostic results of de-novo Bgcox3 PCR were compared with BgITS-1 PCR and Bg18S nPCR. Thin blood smears detected 22% (11/50) samples positive for small form of Babesia species. The BgITS-1 PCR detected 25% samples (15/50) as positive and Bg18S nPCR detected 80% (40/50) B. gibsoni positive samples. The de-novo Bgcox3 PCR detected 66% (33/50) samples positive for B. gibsoni (at 95% CI). The analytical sensitivity of cox3 PCR was evaluated as 0.000003% parasitaemia or 09 parasites in 100 mu l of blood. The de-novo diagnostic cox3 PCR did not cross react with control positive DNA from other haemoprotozoa and rickettsia like B. vogeli, Hepatozoon canis, Trypanosoma evansi, Ehrlichia cants and Anaplasma platys. Statistically, cox3 PCR had better diagnostic efficiency than ITS-1 PCR in terms of sensitivity (p = 0.0006). No statistically significant difference between results of cox3 PCR and 18S nPCR was observed (p = 0.1760). Kappa values estimated for each test pair showed fair to moderate agreement between the observations. Specificity of Bgcox3 PCR was 100% when compared with microscopy or BgITS-1 PCR. Sensitivity of Bgcox3 PCR was 100% when compared with that of Bg18S nPCR.
Keywords: Babesia gibsoni; cox3; Diagnosis; Dog; mitochondria; molecular